2 1 + 4 1 + 8 2 + 1 6 3 + 3 2 5 + 6 4 8 + … = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You need to show that the series converge first else, you will be performing arithmetic on infinities.
This came in yesterday's AMTI paper (Round 1). Sad to say I didn't solve it. =.=
Log in to reply
How was it?
Log in to reply
Alright, I suppose. I got 19/30 questions, missing a few easy ones.
You gave NMTC?
I literally did the same. Even step to step same ^_^ U P V O T E D !
Let B = 2 1 + 4 1 + 8 2 + 1 6 3 + 3 2 5 + . . . *Notice that 4 1 is included. Consider the closed form of the Fibonacci Sequence F n = 5 1 ( 2 1 + 5 ) n − 5 1 ( 2 1 − 5 ) n such that each term of the series B is given by: B n = 5 1 ( 4 1 + 5 ) n − 5 1 ( 4 1 − 5 ) n It is easy to see that the series is actually two geometric series with r 1 = ( 4 1 + 5 ) and r 2 = ( 4 1 − 5 ) and that B = 2 . Since 4 1 is included in B , the answer to the question is B − 4 1 or 1 . 7 5
This series can be written as 2 1 + 4 1 + ∑ n = 3 ∞ 2 n F n .
With the Fibonacci sequence, it is known that F n = F n − 1 + F n − 2 for n ≥ 3 with F 1 = 1 and F 2 = 1 .
Thus, ∑ n = 3 ∞ 2 n F n can be written as ∑ n = 3 ∞ 2 n F n − 1 + F n − 2
which is equal to ∑ n = 3 ∞ 2 n F n − 1 + ∑ n = 3 ∞ 2 n F n − 2 .
Note that the general terms of those series can be put into the form of 2 n F n by shifting indices:
∑ n = 3 ∞ 2 n F n − 1 + ∑ n = 3 ∞ 2 n F n − 2 = 2 1 ∑ n = 2 ∞ 2 n F n + 4 1 ∑ n = 1 ∞ 2 n F n .
Now these series looks very similar to the original. By writing out terms from the series, we can reduce both the series to the form of the original:
2 1 ∑ n = 2 ∞ 2 n F n + 4 1 ∑ n = 1 ∞ 2 n F n = 8 F 1 + 1 6 3 F 2 + 4 3 ∑ n = 3 ∞ 2 n F n .
⟹ ∑ n = 3 ∞ 2 n F n = 8 F 1 + 1 6 3 F 2 + 4 3 ∑ n = 3 ∞ 2 n F n
⟹ ∑ n = 3 ∞ 2 n F n = 1 6 5 + 4 3 ∑ n = 3 ∞ 2 n F n ⟹ ∑ n = 3 ∞ 2 n F n = 4 5 .
This is true due to the convergence of ∑ n = 3 ∞ 2 n F n which can be verified by use of the ratio test which simplifies down to 2 F n F n + 1 which converges to a value less than one as n approaches infinity.
Thus, the answer of 2 1 + 4 1 + ∑ n = 3 ∞ 2 n F n = 2 1 + 4 1 + 4 5 = 4 8 = 2 .
Note that you have to explain why the series converges first (e.g. ratio test), before the arithmetic can be justified.
For example, we still have ∞ = 1 6 5 + 4 3 × ∞ .
Problem Loading...
Note Loading...
Set Loading...
S = 2 1 + 4 1 + 8 2 + 1 6 3 + 3 2 5 + … − ( 1 )
2 1 S = 0 + 4 1 + 8 1 + 1 6 2 + 3 2 3 + … − ( 2 )
Subtracting ( 2 ) from ( 1 ) ,
2 1 S = 2 1 + 8 1 + 1 6 1 + 3 2 2 + 6 4 3 + …
⇒ 2 1 S = 2 1 + 4 1 S
⇒ 4 1 S = 2 1 ⇒ S = 2
Required answer is : − 0 . 2 5 + 2 = 1 . 7 5